Natural compounds with xanthine oxidase inhibitory activity: A review. (24th January 2019) - Mehmood, Arshad; Ishaq, Muhammad; Zhao, Lei; Safdar, Bushra; Rehman, Ashfaq‐ur; Munir, Masooma; Raza, Ali; Nadeem, Muhammad; Iqbal, Waheed; Wang, Chengtao
Abstract: Hyperuricemia (HUA), a disease due to an elevation of body uric acid level and responsible for various diseases such as gout, cardiovascular disorders, and renal failure, is a major ground debate for the medical science these days. Considering the risk factors linked with allopathic drugs for the treatment of this disease, the debate has now become a special issue. Previously, we critically discussed the role of dietary polyphenols in the treatment of HUA. Besides dietary food plants, many researchers figure out the tremendous effects of medicinal plants‐derived phytochemicals against HUA. Keeping in mind all these aspects, we reviewed all possible managerial studies related to HUA through medicinal plants (isolated compounds). In the current review article, we comprehensively discussed various bioactive compounds, chemical structures, and structure–activity relationship with responsible key enzyme xanthine oxidase. Abstract : Purine metabolism results the formation of uric acid in human body due to catalysis of (hypoxanthine and xanthine) by xanthine oxidase enzyme. The over production of uric acid results in hyperuricemia, gout, cardiovascular diseases, etc. Plant drive bioactive compounds bind with xanthine oxidase enzyme due to their special structural features and hinder the entrance of hypoxanthine and xanthine with enzyme, thus prevent from uric acid synthesis.